Open business models : how to thrive in the new innovation landscape - Chesbrough, Henry William (Boston, Mass. : Harvard Business School Press, 2006)
'Open Business Models' introduces a framework called the 'six stages of business model development' and provides diagnostic questions for companies to assess where they are. This framework will help companies articulate what their business model is and show how they can advance along the six-stage continuum.
Why business models need to open up -- The path to open innovation -- The new environment for business models -- The impact of stronger IP upon the business model -- A framework for advancing your business model -- Innovation intermediaries -- IP-enabled business models -- Getting from here to there.
Includes bibliographical references (pages 217-242) and index.
Description based on print version record.
Keywords: Technological innovations -- Management; Research, Industrial -- Management; Innovaciones tecnológicas -- Administración; Investigación industrial -- Administración; Innovations -- Gestion; Recherche industrielle -- Gestion; Vernieuwing; Innovatiediffusie; Paradigma's.; Organisatiestructuur; Openheid; Samenwerking; Research, Industrial -- Management; Technological innovations -- Management; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; elektronické knihy; electronic books